Report of the global online survey to identify key knowledge and capacity gaps on diagnostics and surveillance of pests & diseases in targeted countries - Carvajal-Yepes, Mónica; Cuervo, Maritza; Kreuze, Jan F.; Alakonya, Amos; Kumar, P. Lava; Onaga, Geoffrey; Dawit, Woubit; Castillon, Martina; Kumari, Safaa; Sharma, Rajan; Kawarazuka, Nozomi; Bui, Trang; et al. (2022)
An online survey was co-designed in collaboration with CGIAR Germplasm Health Units (GHUs) leaders and social scientists of the Plant Health Initiative (PHI), with the objective to identify and map the key knowledge and capacity gaps on lab/field detection, characterization, and surveillance of P&D of local and regional NPPOs in targeted countries. The questionnaire consisted of 43 open-ended, single and multiple-choice questions. It was divided into three parts: the first includes questions to collect general information (Institution, country, gender, age group, position, scientific level and role). The second part was aimed to learn and identify current capacities, major challenges, capacity building needs of National Plant Protection Organizations (NPPOs) for pest diagnostics and surveillance. The third part was related to specific questions for early- and mid-career scientists (below 45 years old) to inquire into challenges faced by young and women scientists to identify gender-based constraints. The questionnaire was translated into five different languages (English, Arabic, Spanish, French and Vietnamese), and distributed to NPPOs and national institutions across Latin America and the Caribbean (LAC), Africa, Asia and Central and West Asia and North Africa (CWANA). The report summarizes responses from 52 respondents from 35 institutions across 26 countries.